Political Connection, Public Ownership, Pengungkapan CSR: Peran Moderasi Ukuran Perusahaan - Khairin, Mochamad Yahdi; Firmansyah, Amrie (Politeknik Ganesha Medan, 2024)
Basically, CSR activities are voluntary, but due to regulations set by the government, CSR activities are implicitly mandatory (Xu & Zeng, 2016). The purpose of the government in making regulations related to companies obliged to do CSR is that companies are responsible for the consequences of company operations that may have an impact on the environment and surrounding communities. However, currently the development of CSR disclosure implementation in Indonesia has not been carried out optimally by private companies and state-owned enterprises. According to Nayenggita et al., (2019), the implementation of CSR in Indonesia is currently still carried out based on the perspective of profit sharing which is used to answer desires rather than the needs needed by the community. The purpose of this study is to determine whether political connection and public ownership have an impact on CSR disclosure by using company size as a moderating variable.The data used comes from financial reports and sustainability reports as well as annual reports on state-owned companies listed on the Indonesia Stock Exchange (IDX) in 2020 to 2022. Multiple regression analysis was used to test the hypothesis on the research panel data. The results show that political connection has no effect on CSR disclosure, but public ownership is negatively related to CSR disclosure. The results also concluded that company size can strengthen public ownership. The results also concluded that company size can strengthen the positive effect of public ownership on CSR disclosure.